TEAC research funding proposals considered harmful: ICT research at risk - Clear, Tony (NACCQ, 2003)
As Information Technology (IT) educators, whether career academics or former practitioners, it seems exceedingly rare to find environments in which IT is understood, appropriately managed or nurtured. To expect enlightened goverment policy therefore is perhaps over-optimistic. Yet our Prime Minister has identified the Information & Communications Technology (ICT) sector as a priority. Therefore it seems doubly ironic that the elitist policy now proposed for funding research in the higher education sector promises to further undermine the ability of the IT-related disciplines to prosper in our higher education institutions. Rather then strengthen ICT as a priority sector, current policy directions promise to diminish higher education's contibution to ICT capability building within the nation's innovation framework. This paper reviews the proposed directions and critiques their impact for IT education within the NZ higher eduction sector.